Glossopharyngeal insufflation and pulmonary hemodynamics in elite breath hold divers - Eichinger, Monika; Walterspacher, Stephan; Scholz, Tobias; Tetzlaff, Ralf; Puderbach, Michael; Tetzlaff, Kay; Kopp-Schneider, Annette; Ley, Sebastian; Choe, Kyuok; Kauczor, Hans-Ulrich; Sorichter, Stephan (Medicine and science in sports and exercise, 2010)
Purpose: Acute voluntary lung hyperinflation provoked by glossopharyngeal insufflation (GI) elicits numerous, possibly deleterious, effects on the cardiopulmonary system by increasing intrathoracic pressures far above normal values. This study quantifies acute pulmonary hemodynamics during GI using phase-contrast magnetic resonance imaging (MRI). - Methods: Hemodynamic parameters were measured in nine elite male breath hold divers with a mean age of 30 yr (range = 20-43 yr) by velocity-encoding cine (VEC)-MRI of the main pulmonary artery (PA) before, during, and after GI. Simultaneously, GI-lung volume (GIVEC-MRI) was measured by MR-compatible spirometry. - Results: Hemodynamic parameters were associated with GIVEC-MRI. Highly significant changes during GI were shown for the mean flow in the PA, which decreased by 45% (P < 0.007), and right ventricular output and cardiac index, which decreased by 41% and 40%, respectively (P < 0.007). Acceleration time also decreased highly significant by 36% during GI (P < 0.007). All hemodynamic parameters except acceleration time returned to baseline after GI. - Conclusions: Acute voluntary lung hyperinflation mimics changes seen in pulmonary arterial hypertension, but unlike the latter, these changes are fully reversible shortly after cessation of voluntary lung hyperinflation. Persistent changes due to repetitive GI could not be detected.
Gesehen am 02.03.2023